Desenvolvimento de uma metodologia modelo para obtenção de polissacarídeos de parede celular de resíduos agroindustriais - Menezes, Cristine Soares Vidal de (2020)
The agroindustrial activity generates a large volume of wastes or by-products, and the efficient reuse of these wastes to maximize the use of food matrices is desirable. Among the by-products, we can highlight the peels, bagasse and seeds, which have the potential to be a biomass for the recovery of bioactive compounds such as pectin, lipids, flavonoids, dietary fibers, etc. Pectin is a heteropolysaccharide found in the cell walls of all living plants and acts as a glue between cells. It is widely used in food systems as an emulsifying, stabilizing and thickening agent. However, there are several methods to extract these bioactive compounds and they do not follow a standard methodology, making it difficult to achieve selectivity and reproducibility with respect to the extracted material. Therefore, the aim of this work was to extract polysaccharides from the cell wall of Mangifera indica, Passiflora eduli, Anacardium occidentale, Cocos nucifera and Saccharum officinarum using a standard methodology for reliable extraction. The fractions were obtained from sequential extraction protocols with water, cyclohexane-trans-1,2-diamine tetracetate (CDTA), sodium carbonate / CDTA and KOH, and the fractions were named water-soluble pectin (WSP), CDTA-soluble pectin (CSP), sodium carbonate-soluble pectin (SSP) and hemicellulose (HC), respectively. Fourier transform infrared spectroscopy (FTIR), gel permeation chromatography (GPC) and hydrogen nuclear magnetic resonance (1H NMR), carbon nuclear magnetic resonance (13C NMR) and heteronuclear single quantum coherence spectroscopy (HSQC) were used to characterize each of the cell wall polysaccharide fractions. The spectra of the WSP, CSP and SSP fractions of all materials studied showed characteristic signs of pectin residues and the HC fraction showed hemicellulose features. These results showed that the methodology used as a standard protocol for the bioactive extraction of agroindustrial wastes is reproducible and reliable, since the fractions were similar regardless of the material.